PENERAPAN AKUNTANSI SOSIAL EKONOMI TERHADAP TANGGUNGJAWAB SOSIAL PADA PT. PUPUK ISKANDAR MUDA KABUPATEN ACEH UTARA - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2020)
This study aims to determine the effect of social economic accounting application on social responsibility on PT. Pupuk Iskandar Muda (PIM) Kabupaten Aceh Utara. The samples used in this study were 87 employess on PT. Pupuk Iskandar Muda (PIM) Kabupaten Aceh Utara. This study uses a stratified random sampling technique from the total number of 681 employees PT. Pupuk Iskandar Muda (PIM) Kabupaten Aceh Utara. The data analysis technique used is simple linear regression analysis. Research results show that social economic accounting have a significant effect on social responsibility at PT. Pupuk Iskandar Muda (PIM) Kabupaten Aceh Utara. With a value of t count of 7.579 with a significant level of 0,000 t table amounting to 1.663.